Antioxidant capacity and proximal analysis of Solanum sessiliflorum Dunal and Chenopodium quinoa Willdenow nectar-based - Quispe-Herrera, Rosel (2022)
Introduction. Several studies have shown that the fruit of cocona and quinoa seeds have good levels of nutritional and functional compounds, as well as great versatility for food preparation. Objective. To determine the taste attribute preference, the physicochemical profile and the antioxidant capacity of the nutraceutical drink nectar based on S. sessiliflorum Dunal (cocona) enriched with Chenopodium quinoa Willdenow (quinoa). Materials and methods. A nectar was prepared with cocona pulp and quinoa seeds variety INIA 415 Pansakalla, under the Peruvian Technical Standard (NTP 203.110 2009) with fruits collected between February and March 2019, in the town center of Santa Rosa, Inambari district, Tambopata province, department of Madre de Dios, Peru. A sensory panel of forty people evaluated the flavor attribute, the proximal composition was determined by standardized methods and antioxidant capacity by ABTS methodology. Results. The most preferred nectar contained 73 % cocona pulp and 7 % cooked quinoa, the addition of quinoa increased the macronutrient content by 42 %, as well as the antioxidant capacity by 20 %. The cooked quinoa grains presented double the antioxidant capacity compared to cocona fruit. A low-calorie beverage was obtained (49.3 kcal/100 g) and enriched with bioactive compounds of high antioxidant capacity. Conclusions. The formulation with the highest acceptance according to the flavor attribute, physicochemical profile, and antioxidant capacity of the beverage was the one containing a proportion of 73 % cocona pulp and 7 % cooked quinoa grains, a beverage that met the regulatory requirements and could contribute to maintain and improve health.